2006
DOI: 10.1146/annurev.micro.60.080805.142106
|View full text |Cite
|
Sign up to set email alerts
|

Curli Biogenesis and Function

Abstract: Curli are the major proteinaceous component of a complex extra-cellular matrix produced by many Enterobacteriaceae. Curli were first discovered in the late 1980s on Escherichia coli strains that caused bovine mastitis, and have since been implicated in many physiological and pathogenic processes of E. coli and Salmonella spp. Curli fibers are involved in adhesion to surfaces, cell aggregation, and biofilm formation. Curli also mediate host cell adhesion and invasion, and they are potent inducers of the host in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
1,045
2
20

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,027 publications
(1,081 citation statements)
references
References 97 publications
14
1,045
2
20
Order By: Relevance
“…Using a macrocolony assay, we could show that more than half of our tested strains from both investigated sets were able to produce curli fibres and the exopolysaccharide cellulose which are necessary to form stable and strong biofilm matrices (Olsen et al ., 1989; Barnhart and Chapman, 2006; Uhlich et al ., 2006; Serra et al ., 2013, 2015). These positive strains were isolated from all the seven investigated flocks by Daehre et al .…”
Section: Discussionmentioning
confidence: 99%
“…Using a macrocolony assay, we could show that more than half of our tested strains from both investigated sets were able to produce curli fibres and the exopolysaccharide cellulose which are necessary to form stable and strong biofilm matrices (Olsen et al ., 1989; Barnhart and Chapman, 2006; Uhlich et al ., 2006; Serra et al ., 2013, 2015). These positive strains were isolated from all the seven investigated flocks by Daehre et al .…”
Section: Discussionmentioning
confidence: 99%
“…Those appendices are shafts protruding from the bacterial cell surface and comprise different proteins (Wu and Fives-Taylor, 2001;Bann et al, 2002;Clarke et al, 2003;Mainil, 2003aMainil, , 2005aBarnhart and Chapman, 2006). Structurally the shaft is made of several hundreds copies of a protein, whose generic name is "major subunit" of a molecular weight between 15 and 20 kDa, but that received different other names according to the actual appendix (pilin, fimbrin, or curlin f.i.).…”
Section: The Appendicesmentioning
confidence: 99%
“…Curli may be involved in the adherence of SePEC to the mucosal extracellular matrix after fragilization of the epithelium and in the formation of biofilm on organic (not only animals, but also plants) and non-organic surfaces by O157:H7 EHEC and other pathogenic strains. But more studies are needed, especially in vivo to more precisely understand their role in E. coli pathogenicity (Wu and Fives-Taylor, 2001; Barnhart and Chapman, 2006;Goulter et al, 2009;Saldana et al, 2011).…”
Section: The Appendicesmentioning
confidence: 99%
“…Several examples have now been described in which the amyloid structure serves an apparently normal physiologic function, notably the curli protein of escherichia coli, yeast prions and the melanosome melanin binding protein Pmel17. [13][14][15] Our discussions in this review will cover only those conditions in which tissue deposits fulfilling the pathologic criteria for amyloid, that is, Congophilia, ultrastructurally fibrillar, co-deposited SAP, ApoE and Perlecan, are found. For the most part the deposits are extracellular, although there are now instances in which it has been reported that the earliest steps in aggregation can be seen intracellularly.…”
Section: A Protein Preamblementioning
confidence: 99%